Corroborating catch estimates to inform monitoring of a small-scale marine recreational fishery in a World Heritage property. (1st June 2021) - Taylor, S M; Smallwood, C B; Desfosses, C J; Ryan, K L; Jackson, G
Abstract: Obtaining accurate estimates of catch can be challenging for small-scale recreational fisheries. Using inner Shark Bay as a case-study, we investigated whether a state-wide phone-diary (PD) survey could provide robust estimates of boat-based fishing effort and catch (kept and total) of pink snapper ( Chrysophrys auratus ) and grass emperor ( Lethrinus laticaudis ). Estimates were compared with those from concurrent surveys for two spatial scales corresponding to the fishery and the three pink snapper stocks within the fishery. A supplementary access point (SAP) survey incorporated remote camera data and interviews with fishers at boat ramps. An aerial survey was used to adjust the SAP estimates, accounting for catches from boat fishers launching from remote beaches (SAP_Aerial). The SAP survey provided the most precise estimates but underestimated catches for one of the stocks. Estimated fishing effort from the SAP_Aerial survey was comparable to the PD survey (3% lower) for inner Shark Bay, as was the estimated kept catch of pink snapper (7% lower) and these estimates were considered robust (Relative Standard Error < 40% and sample size ≥ 30). In contrast, estimates of the total catch of pink snapper and the catch (kept and total) of grass emperor from the PD survey were consistently lower. While the on-site surveys generally provided robust estimates of catch for each stock, most PD estimates were not robust at this scale. The SAP_Aerial survey is considered to be the most appropriate for ongoing monitoring because it provides robust estimates for the spatial scales examined. However, estimates of catch from periodic PD surveys for the entire fishery could be adjusted using the on-site data to provide the stock-specific information required for ongoing assessments of sustainability. Our study demonstrates that corroborative studies assist in monitoring recreational fisheries.